A method for recycling scrap steel to prepare high-strength ductile iron material
By recycling scrap steel and adopting a specific process flow to control the element content and distribution, the problems of high production costs and insufficient performance of traditional ductile cast iron are solved, and high strength and low cost are achieved.
Patent Information
- Application Number
- CN202411089609.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-08-09
- Publication Date
- 2025-02-18
- Estimated Expiration
- 2044-08-09
AI Technical Summary
Traditional ductile iron production requires a large amount of high-cost pig iron, and its performance is affected by the structure, trace elements and defects, making it difficult to achieve both high strength and low cost.
By recycling scrap steel and adopting specific process flows, including smelting, spheroidization, flow-based growth and heat treatment, the content and distribution of elements such as carbon, silicon, manganese, and copper are controlled to form high-strength ductile iron.
The preparation of high-strength ductile iron is realized, which improves the tensile strength, impact performance and wear resistance of the material, and reduces production costs.
Smart Images

Figure 677F99D32D9AD 
Figure 677F99D392579
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of scrap steel recycling and processing, in particular to a method for recycling scrap steel to prepare high-strength ductile iron material. Background Art
[0002] Ductile iron is a type of cast iron in which graphite exists in spherical form. Its comprehensive properties are close to those of steel, with medium to high strength and toughness, good wear resistance, vibration damping, and casting process performance. The production of traditional ductile iron requires a large amount of foundry pig iron, which is relatively expensive. In addition, pig iron has heredity, which is manifested in the retention and inheritance of organizational structure characteristics, trace elements, defects, etc.; the production of high-purity pig iron is more difficult and more expensive. However, the amount of scrap steel precipitated is large and the price is low. It is obtained through blast furnace smelting, oxidation-reduction, refining and other processes, and the content of impurities such as S and P is low. Therefore, a large number of foundries use scrap steel carburization technology to replace foundry pig iron to produce low-cost, high-performance ductile iron castings.
[0003] The microstructure of ductile iron is composed of ferrite, pearlite and spheroidal graphite distributed on it. The mechanical properties of ductile iron are greatly affected by its microstructure, which is mainly reflected in the following aspects: 1. The graphite morphology in the microstructure, reducing the size of graphite nodules, increasing the graphite spheroidization rate and the uniform distribution of graphite nodules can improve the strength and plasticity of ductile iron; 2. The increase of ferrite content in the microstructure is conducive to the improvement of plasticity and toughness of ductile iron; 3. The increase of pearlite content in the microstructure is conducive to the improvement of strength and wear resistance of ductile iron.
[0004] High-performance ductile iron is mainly divided into pearlite ductile iron and austempered ductile iron. Austempered ductile iron has high comprehensive performance, but its processing performance is poor due to high hardness and work hardening. Pearlite ductile iron has better processability and higher applicability, but its comprehensive performance is not good. Therefore, we propose a method for recycling scrap steel to prepare high-strength ductile iron material. Summary of the invention
[0005] The object of the present invention is to provide a method for recycling scrap steel to prepare high-strength ductile iron material, so as to solve the problems raised in the above background technology.
[0006] In order to solve the above technical problems, the present invention provides the following technical solution: a method for recycling scrap steel to prepare high-strength ductile iron material, comprising the following process:
[0007] Step 1. Smelting: Add scrap steel and carburizer into the furnace in sequence, heat and melt to 1500-1560°C until the carburizer is completely melted; add ferrosilicon and copper to form molten iron;
[0008] Step 2. Spheroidizing and inoculating: add spheroidizing agent to the bottom of the spheroidizing bag, cover the spheroidizing agent with primary inoculant, pour the molten iron into the spheroidizing bag, control the temperature at 1430-1460℃, and carry out inoculation in the mold while spheroidizing;
[0009] After being poured out of the furnace, a flow inoculant is added during the process for flow inoculation; after cooling and forming, heat treatment is performed to obtain ductile iron.
[0010] Furthermore, the composition of the scrap steel is as follows: in mass percentage, carbon C: 0.14-0.30%, silicon Si: 0.25-0.35%, manganese Mn: ≤0.3%, phosphorus P: ≤0.04%, sulfur S: ≤0.03%, other impurities content <0.1%, and the balance is iron Fe.
[0011] Furthermore, in step 2, the furnace temperature is 1420-1460° C.; the pouring temperature is 1300-1360° C., and the pouring is completed within 30 minutes.
[0012] Furthermore, the ductile iron includes the following components: in mass percentage, carbon C: 3.4-3.9%, silicon Si: 2.2-3.0%, manganese Mn: 0.3-0.6%, copper Cu: 0.5-0.8%, magnesium Mg: 0.03-0.06%, phosphorus P: <0.10%, sulfur S: <0.03%, rare earth elements RE: 0.02-0.05%, nitrogen N: 50-120ppm, zirconium Zr: 0.015-0.040%, and the balance is iron Fe.
[0013] Further, in the mass composition of ductile iron, C+Si / 3=4.3-4.6%;
[0014] Mn+Cu:<1.20%, Si / 2≥Mn+Cu.
[0015] Furthermore, the rare earth element is a mixture of multiple rare earth elements, and in terms of mass percentage, RE=55% cerium Ce+28% lanthanum La+17% neodymium Nd.
[0016] In the above technical solution, the graphitization process of carbon element is at the stable equilibrium temperature T EG and the metastable system equilibrium temperature T EM Cr, Mn, and V reduce the T EG -T EM Temperature range, making it easy to produce carbides in ductile iron structure. Silicon can strongly weaken the Fe-C bond and expand T EG -T EM Interval, improve T EGTemperature effectively inhibits the precipitation of carbides. However, the increase in silicon content will reduce the plasticity and toughness of ductile iron, so the silicon content needs to be controlled. Carbon equivalent CE (C+Si / 3) is used to indicate the ability of carbon and silicon content to promote the degree of graphitization. The increase in carbon content increases the number of crystallized graphite (balls) in ductile iron, and the graphite balls tend to be refined and rounded, but too high carbon content or carbon equivalent will affect graphite floating; too much silicon will damage the low-temperature impact properties of ductile iron. Therefore, the content of both needs to be controlled.
[0017] Manganese can stabilize and refine pearlite, increase the content of pearlite, and improve the tensile strength and hardness of the produced ductile iron; however, it will reduce the plasticity of ductile iron, and manganese is an element that hinders graphitization and will reduce T EG -T EM In the temperature range, there is a tendency of segregation in ductile iron, and the manganese content on the grain boundary is higher than that in the grain. In severe cases, carbides will be formed, which will increase the brittleness of ductile iron and lead to a decrease in the performance of ductile iron. The added copper element can promote graphitization in the eutectic stage, reduce the formation of free carbides, improve the graphite morphology, increase the roundness of graphite balls, increase the number of graphite, refine the size of graphite, and improve the uniformity of the organization; during the eutectoid transformation, it can promote the formation of pearlite, stabilize and refine the pearlite, and play a role in solid solution strengthening and precipitation hardening; and as its content increases, the tensile strength of the ductile iron produced increases, and the elongation after fracture decreases. Therefore, the content of the two elements needs to be controlled. Silicon, manganese, and copper elements all have a solid solution effect on ferrite. While silicon enhances the transformation of ferrite, it will promote the coarsening of pearlite. The addition of copper and manganese alleviates this phenomenon. In order to take into account the strength and toughness of ductile iron, the relative content of the three elements needs to be controlled.
[0018] Magnesium is a common spheroidizing element in ductile iron. Too high magnesium content will aggravate the tendency of cast iron to produce white cast iron. Sulfur and phosphorus are harmful elements. Among them, phosphorus will form a multi-phosphorus eutectic in ductile iron, which will increase the brittleness of ductile iron and reduce its elongation. Sulfur will react with graphitizing elements, resulting in unstable spheroidization of the system. Therefore, it is necessary to control the content of both in order to obtain high-strength ductile iron.
[0019] Rare earth elements can promote spheroidization and are generally combined with magnesium to ensure the best spheroidization effect of the system. However, too much rare earth will destroy the shape of graphite, causing it to deform, the spheroidization level will deteriorate, and the strength and toughness of ductile iron will decrease.
[0020] Furthermore, the recarburizer is a mixture of one or more of coke, graphite and silicon carbide.
[0021] In the above technical solution, silicon carbide can react with iron to generate FeSi and non-equilibrium carbon, which is easy to absorb carbon in molten iron, so that crystal nuclei can be formed in large quantities in a short time, and have a lasting nucleation effect, and the number of grains is increased. As silicon carbide melts and releases a large amount of heat to the surroundings, the nucleation temperature is increased, the growth of grains is inhibited, fine grain strengthening is achieved, the eutectic cooling curve moves up, the precipitation of graphite is promoted, and the precipitation of carbides can be inhibited.
[0022] Furthermore, in step 2, the spheroidizing agent is rare earth silicon-iron-magnesium alloy and manganese nitride, and the amount of manganese nitride added is 0.1 to 0.3% of the mass of the original molten iron.
[0023] In the above technical scheme, the rare earth in the spheroidizing agent can neutralize the trace harmful elements remaining in the scrap steel. Manganese nitride is added during the spheroidizing process. While adding manganese, a trace amount of nitrogen (50-120ppm) is introduced into the molten iron, and the manganese element helps to improve the solubility of nitrogen. The atomic radius of nitrogen atoms is small, and they can be dissolved in the iron matrix to form interstitial solid solutions, strengthen the organization, exert microalloying effects, play a role in solid solution strengthening, stabilize austenite, and promote the formation, stabilization, refinement and spacing reduction of pearlite. Nitrogen is dissolved in carbon and can inhibit the formation of cementite; it is adsorbed on the surface of graphite, inhibiting the diffusion of carbon atoms in molten iron to graphite, hindering the growth of graphite, and contributing to the spheroidization of graphite and its size refinement, further improving the performance of ductile iron.
[0024] Further, in step 2, the primary inoculant is 75SiFe;
[0025] The flow inoculant is a zirconium-containing inoculant, and the flow inoculant includes the following components: in mass percentage, Zr: 15-40%, Si: 40-70%, C: <0.5%, S: <0.02%, P: <0.04%, Mn: <0.2%, Al: <1.5%, and the balance is Fe.
[0026] In the above technical solution, when Si element is added to molten iron in the form of FeSi inoculant, it can serve as nucleation points of graphite in the molten iron, thereby promoting the formation of graphite.
[0027] The flow inoculant uses a zirconium-containing inoculant, in which the zirconium element can neutralize the influence of nitrogen in the molten iron, prevent the occurrence of nitrogen pore defects, and eliminate the adverse effects of the spheroidization process; it can also reduce the supercooling of the molten iron, promote the spheroidization of graphite, increase the spheroidization rate of ductile iron, and further improve its comprehensive mechanical properties. Zirconium can form interstitial phase zirconium carbide with high melting point and high hardness with free carbon, thereby improving the surface hardness and wear resistance of the ductile iron. The addition of zirconium in the flow inoculation process can effectively avoid its occupation of carbon, and the generated carbides have a negative impact on the organizational properties of ductile iron.
[0028] Furthermore, the heat treatment process is: heating to 850-880°C, keeping the temperature for 90-120 minutes; air cooling;
[0029] Raise the temperature to 260-280°C, keep the temperature and react for 45-90 minutes; air cool.
[0030] In the above technical solution, the generated ductile iron is austenitized and isothermally transformed by heat treatment. The ductile iron formed after pouring and cooling has a cast structure mainly composed of pearlite, and the rest is ferrite and graphite nodules. After isothermal quenching, it is transformed into acicular ferrite, high carbon austenite and graphite nodules.
[0031] At high temperatures, pearlite and ferrite undergo austenitization. The carbon concentration of austenite is between that of ferrite and cementite, which makes it preferentially nucleate at the interface between ferrite and cementite. There are a large number of ferrite and cementite interfaces in pearlite, and the nucleation interface is larger, which helps to increase the number of austenite grains and refine their size. Too high a temperature will cause the dissolution and diffusion of graphite, and too long a heat preservation time will cause the size of austenite to grow, which will affect the strength and toughness of ductile iron.
[0032] Then, isothermal quenching is performed, and ferrite nucleates and grows at the austenite grain boundary or the grain boundary between it and graphite to form needle-shaped ferrite. The small-sized high-temperature austenite grains formed after austenitization increase the number of grain boundaries, and the growth of ferrite stops at the interface, which can promote the refinement of ferrite. Lower temperatures are conducive to the refinement of austenite and ferrite grains, which can effectively improve the mechanical strength of ductile iron.
[0033] Furthermore, the ductile iron is surface treated, and the specific process is as follows:
[0034] S1. Mix and disperse carboxylated graphene and ammonium metatungstate solution; heat to 60-70°C, stir for 4-5h; filter and dry;
[0035] Under the protection of nitrogen atmosphere, the temperature is raised to 900-950°C, and a mixed gas of hydrogen and methane is introduced at the same time, and the temperature is kept for reaction for 4-5 hours; and the mixture is cooled naturally to obtain composite material A;
[0036] S2. The composite material A is mixed with boron carbide, ball-milled with ethanol, dried, and passed through a 100-mesh sieve; cold isostatic pressing and sintering are performed to obtain a composite material B;
[0037] S3. The composite material B and iron powder are mixed, ball-milled, cold-pressed, hot-pressed, sintered, and crushed to obtain a composite material C;
[0038] S4. Spray the composite material C onto the surface of the ductile iron and perform plasma beam modification to obtain a ductile iron material.
[0039] Further, in S1, the volume ratio of carboxylated graphene and ammonium metatungstate solution is 1:(5-10);
[0040] The concentration of ammonium metatungstate solution is 15-50wt%;
[0041] In the mixed gas, the volume ratio of hydrogen to methane is 1:10.
[0042] Furthermore, in S2, the mass ratio of composite material A and boron carbide is (8-10):(2.5-3.7); and the solid-liquid ratio is 1:0.8.
[0043] Further, in S2, the process conditions of cold isostatic pressing are: pressure 160-200 MPa, time 180-200 s;
[0044] The sintering process conditions are: vacuum, 900-950°C, heat preservation for 60-90 minutes;
[0045] Under argon atmosphere, heat up to 1600-1650°C and keep warm for 60-90 min; heat up to 2150-2200°C and keep warm for 100-150 min.
[0046] Further, in S3, the particle size of the composite material C is 5 to 8 μm;
[0047] Composite material B is 12-30% of the mass of iron powder;
[0048] The process conditions of cold pressing are: pressure 16-24 MPa, duration 3-4 h;
[0049] The sintering process conditions are: hot pressing pressure 15-18MPa, in argon atmosphere, at 700-750°C, keep warm for 160-200min; heat up to 1200-1250°C, keep warm for 160-200min; cool down to 450-480°C, keep warm for 100-150min; cool to room temperature with the furnace.
[0050] Further, in S4, the spraying thickness of the composite material C is 0.5 to 1.0 mm;
[0051] The process conditions of plasma beam modification are: current 30-50A; argon gas flow rate 5-8L / min; scanning speed 500-800mm / min.
[0052] In the above technical scheme, ammonium metatungstate is used to modify the metal tungsten ions onto the surface of carboxylated graphene. At high temperature, the tungsten ions are reduced by in-situ carbon to form carbides to obtain a tungsten carbide-graphene composite material, which is recorded as composite material A. The composite material is ball-milled and mixed with boron carbide, and then sintered, so that boron carbide reacts with tungsten carbide to form tungsten boride and pyrolytic carbon, and combined with unreacted graphene to obtain composite material B. Composite material C prepared by composite material B and iron powder is sprayed on the surface of ductile iron, and the ductile iron is surface treated by plasma beam to infiltrate the cast iron matrix to form a composite layer. The composite layer contains dispersed superhard material tungsten boride, and the structure of the composite layer is strengthened, which can significantly improve the surface hardness of the ductile iron material and improve its wear resistance; and it has an inhibitory effect on the plastic deformation caused by dislocation movement and crack propagation. In addition, the introduction of good graphene with strong toughness into the composite layer has a difference in thermal expansion coefficient, which can prevent the growth of grains in the composite layer, refine the structure and grains of the composite layer, and thus improve its comprehensive performance. In addition, the carbon produced by pyrolysis penetrates into the surface of the ductile iron material during the process, increasing its surface carbon content and alleviating the impact of the plasma beam on the graphite on the surface of the ductile iron. While ensuring its strength, it can further improve its surface hardness and wear resistance and friction reduction performance. DETAILED DESCRIPTION
[0053] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0054] In the following specific implementations,
[0055] The composition of the scrap steel is as follows: by mass percentage, C: 0.23%, Si: 0.27%, Mn: 0.26%, P: 0.032%, S: ≤ 0.025%, and the balance is Fe;
[0056] Carbon raiser: graphitized carbon raiser, C ≥ 99%, S ≤ 0.03%, average particle size 5mm, from Shandong Keen Carbon Materials Co., Ltd.;
[0057] Ferrosilicon: from Qinghai Fuxin Silicon Industry Co., Ltd.;
[0058] Copper: purity ≥99.99%, sourced from Shanghai Yili Metal Materials Co., Ltd.;
[0059] Rare earth silicon iron magnesium alloy: average particle size 7mm, sourced from Suzhou Haichuan Rare Metal Products Co., Ltd.;
[0060] Manganese nitride: average particle size 6mm, from Gaide Chemical;
[0061] Primary inoculant: 75SiFe, average particle size 3mm, from Nangong Jingrui Alloy Products Co., Ltd.;
[0062] Flow inoculant: FeSiZr30, average particle size 0.4 mm, from Xi'an Qinli Alloy Material Technology Co., Ltd.;
[0063] Carboxylated graphene: diameter 1-5um, thickness 0.8-1.2nm, carboxyl ratio 5.0%, purity 99%, from Shanghai Zhenzhun Biotechnology Co., Ltd.;
[0064] Boron carbide: purity ≥99.9%, 50nm, from Shanghai Yaotian New Materials Technology Co., Ltd.;
[0065] Iron powder: purity ≥99.9%, 50nm, from Shanghai Xiaohuang Nanotechnology Co., Ltd.;
[0066] Tungsten carbide: DK-WC-002, from Beijing Dekedaojin Technology Co., Ltd.;
[0067] In Examples 1-3, the ductile iron includes the following components: in mass percentage, C: 3.7%, Si: 2.6%, Mn: 0.35%, Cu: 0.7%, Mg: 0.04%, P: 0.005%, S: 0.012%, RE: 0.021% (55% Ce+28% La+17% Nd), N: 100 ppm, Zr: 0.030%, and the balance is Fe.
[0068] Example 1: A method for recycling scrap steel to prepare high-strength ductile iron material, comprising the following process:
[0069] Step 1. Smelting: Add scrap steel and carburizer into the furnace in sequence, heat and melt to 1500℃ until the carburizer is completely melted; add ferrosilicon and copper to form molten iron;
[0070] Step 2. Spheroidizing inoculation: add spheroidizing agent (1.5% rare earth silicon-iron-magnesium alloy and 0.2% manganese nitride, relative to the original molten iron) to the bottom of the spheroidizing bag, cover the spheroidizing agent with 1.0% primary inoculant, pour the original molten iron into it, control the temperature at 1430℃, and carry out inoculation in the mold while spheroidizing;
[0071] The furnace is poured, the furnace temperature is 1440℃, the pouring temperature is 1330℃, and 0.2% of the flow inoculant is added during the process for flow inoculation; after cooling and molding, heat treatment is carried out, the process is: heating to 850℃, keeping the temperature for 120min; air cooling; heating to 260℃, keeping the temperature for 90min; air cooling, and ductile iron is obtained;
[0072] Step 3. Surface treatment:
[0073] S1. Mix and disperse carboxylated graphene and 15wt% ammonium metatungstate solution; heat to 60°C, stir for 4h; filter and dry; heat to 900°C under nitrogen atmosphere, and introduce a mixture of hydrogen and methane in a volume ratio of 1:10, and keep warm for 4h; cool naturally to obtain composite material A; the volume ratio of carboxylated graphene and ammonium metatungstate solution is 1:5;
[0074] S2. Composite material A was mixed with boron carbide, and ethanol was added for ball milling, with a solid-liquid ratio of 1:0.8, dried, and passed through a 100-mesh sieve; cold isostatic pressing, the process was: pressure 160MPa, duration 200s; sintering, in vacuum, 900°C temperature, heat preservation for 90min; in argon atmosphere, the temperature was raised to 1600°C, heat preservation for 60min; the temperature was raised to 2150°C, heat preservation for 100min, and composite material B was obtained; the mass ratio of composite material A to boron carbide was 8:2.5;
[0075] S3. Composite material B and iron powder were mixed, ball-milled, cold-pressed, and the process was: pressure 16MPa, duration 4h; hot-pressed sintering, the process was: hot-pressing pressure 15MPa, in argon atmosphere, at 700℃, keep warm for 160min; heated to 1200℃, keep warm for 160min; cooled to 450℃, keep warm for 100min; cooled to room temperature with the furnace; crushed to obtain composite material C with a particle size of 8μm; composite material B was 12% of the mass of iron powder;
[0076] S4. Spray the composite material C onto the surface of the ductile iron with a spraying thickness of 0.5, and perform plasma beam modification. The process is: current 30A; argon gas flow rate 5L / min; scanning speed 500mm / min, to obtain ductile iron material.
[0077] Example 2: A method for recycling scrap steel to prepare high-strength ductile iron material, comprising the following process:
[0078] Step 1. Smelting: Add scrap steel and carburizer into the furnace in sequence, heat and melt to 1530°C until the carburizer is completely melted; add ferrosilicon and copper to form molten iron;
[0079] Step 2. Spheroidizing inoculation: Add spheroidizing agent (1.5% rare earth silicon-iron-magnesium alloy and 0.2% manganese nitride, relative to the original molten iron) to the bottom of the spheroidizing bag, cover the spheroidizing agent with 1.0% primary inoculant, pour the original molten iron into it, control the temperature at 1450℃, and carry out inoculation in the mold while spheroidizing;
[0080] The furnace is poured, the furnace temperature is 1440℃, the pouring temperature is 1330℃, and 0.2% of the flow inoculant is added during the process for flow inoculation; after cooling and molding, heat treatment is carried out, the process is: heating to 860℃, keeping the temperature for 105min; air cooling; heating to 270℃, keeping the temperature for 60min; air cooling, and ductile iron is obtained;
[0081] Step 3. Surface treatment:
[0082] S1. Mix and disperse carboxylated graphene and 30wt% ammonium metatungstate solution; heat to 65°C, stir for 4.5h; filter and dry; heat to 920°C under nitrogen atmosphere, and introduce a mixture of hydrogen and methane in a volume ratio of 1:10, and keep warm for 4.5h; cool naturally to obtain composite material A; the volume ratio of carboxylated graphene and ammonium metatungstate solution is 1:8;
[0083] S2. Composite material A was mixed with boron carbide, and ethanol was added for ball milling, with a solid-liquid ratio of 1:0.8, dried, and passed through a 100-mesh sieve; cold isostatic pressing, the process was: pressure 180 MPa, duration 190 s; sintering, in vacuum, 920 ° C temperature, heat preservation for 75 min; in argon atmosphere, heating to 1620 ° C, heat preservation for 75 min; heating to 2170 ° C, heat preservation for 120 min, to obtain composite material B; the mass ratio of composite material A to boron carbide was 9:3;
[0084] S3. Composite material B and iron powder were mixed, ball-milled, cold-pressed, and the process was: pressure 20MPa, duration 3.5h; hot-pressed sintering, the process was: hot-pressing pressure 16MPa, in argon atmosphere, at 720℃, keep warm for 180min; heated to 1220℃, keep warm for 180min; cooled to 460℃, keep warm for 120min; cooled to room temperature with the furnace; crushed to obtain composite material C with a particle size of 8μm; composite material B was 22% of the mass of iron powder;
[0085] S4. Spray the composite material C onto the surface of the ductile iron with a spraying thickness of 0.5 mm, and perform plasma beam modification. The process is as follows: current 30 A; argon gas flow rate 5 L / min; scanning speed 500 mm / min, to obtain ductile iron material.
[0086] Embodiment 3: A method for recycling scrap steel to prepare high-strength ductile iron material, comprising the following process:
[0087] Step 1. Smelting: Add scrap steel and carburizer into the furnace in sequence, heat and melt to 1560°C until the carburizer is completely melted; add ferrosilicon and copper to form molten iron;
[0088] Step 2. Spheroidizing inoculation: add spheroidizing agent (1.5% rare earth silicon-iron-magnesium alloy and 0.2% manganese nitride, relative to the original molten iron) to the bottom of the spheroidizing bag, cover the spheroidizing agent with 1.0% primary inoculant, pour the original molten iron into it, control the temperature at 1460℃, and carry out inoculation in the mold while spheroidizing;
[0089] The furnace is poured, the furnace temperature is 1440℃, the pouring temperature is 1330℃, and 0.2% of the flow inoculant is added during the process for flow inoculation; after cooling and molding, heat treatment is carried out, the process is: heating to 880℃, keeping the temperature for 90min; air cooling; heating to 280℃, keeping the temperature for 45min; air cooling, and ductile iron is obtained;
[0090] Step 3. Surface treatment:
[0091] S1. Mix and disperse carboxylated graphene and 50wt% ammonium metatungstate solution; heat to 70°C, stir for 5h; filter, dry; heat to 950°C under nitrogen atmosphere, and introduce a mixture of hydrogen and methane in a volume ratio of 1:10, and keep warm for 5h; cool naturally to obtain composite material A; the volume ratio of carboxylated graphene and ammonium metatungstate solution is 1:10;
[0092] S2. Composite material A was mixed with boron carbide, and ethanol was added for ball milling, with a solid-liquid ratio of 1:0.8, dried, and passed through a 100-mesh sieve; cold isostatic pressing, the process was: pressure 200MPa, duration 180s; sintering, in vacuum, 950°C temperature, heat preservation for 60min; in argon atmosphere, heating to 1650°C, heat preservation for 90min; heating to 2200°C, heat preservation for 150min, to obtain composite material B; the mass ratio of composite material A to boron carbide was 10:3.7;
[0093] S3. Composite material B and iron powder were mixed, ball-milled, cold-pressed, and the process was: pressure 24MPa, duration 3h; hot-pressed sintering, the process was: hot-pressing pressure 18MPa, in argon atmosphere, at 750℃, keep warm for 200min; heated to 1250℃, keep warm for 200min; cooled to 480℃, keep warm for 150min; cooled to room temperature with the furnace; crushed to obtain composite material C with a particle size of 8μm; composite material B was 30% of the mass of iron powder;
[0094] S4. Spray the composite material C onto the surface of the ductile iron with a spraying thickness of 1.0 mm, and perform plasma beam modification. The process is as follows: current 50 A; argon gas flow rate 8 L / min; scanning speed 800 mm / min, to obtain ductile iron material.
[0095] Comparative Example 1: A method for recycling scrap steel to prepare high-strength ductile iron material, comprising the following process:
[0096] Step 1. Smelting: adding manganese element during smelting; Step 2. No manganese nitride is added during spheroidizing inoculation, and no flow inoculation is performed; The heat treatment process is: heating to 850°C, keeping the temperature for 120 minutes; air cooling; heating to 560°C, keeping the temperature for 90 minutes; air cooling, and obtaining ductile iron;
[0097] Ductile iron includes the following components: by mass percentage, C: 3.7%, Si: 2.6%, Mn: 0.33%, Cu: 0.7%, Mg: 0.04%, P: 0.01%, S: 0.017%, RE: 0.020% (55% Ce + 28% La + 17% Nd), the balance is Fe
[0098] The other processes are the same as those in Example 1 to obtain ductile iron material.
[0099] Comparative Example 2: A method for recycling scrap steel to prepare high-strength ductile iron material, comprising the following process:
[0100] Steps 1-2 are the same as in Example 1.
[0101] Step 3. Surface treatment:
[0102] S1. Mix and disperse carboxylated graphene and 15wt% ammonium metatungstate solution; heat to 60°C, stir for 4h; filter and dry; heat to 900°C under nitrogen atmosphere, and introduce a mixture of hydrogen and methane in a volume ratio of 1:10, and keep warm for 4h; cool naturally to obtain composite material A; the volume ratio of carboxylated graphene and ammonium metatungstate solution is 1:5;
[0103] S3. Composite material A and iron powder were mixed, ball-milled, cold-pressed, and the process was: pressure 16MPa, duration 4h; hot-pressed sintering, the process was: hot-pressing pressure 15MPa, in argon atmosphere, at 700℃, keep warm for 160min; heated to 1200℃, keep warm for 160min; cooled to 450℃, keep warm for 100min; cooled to room temperature with the furnace; crushed to obtain composite material B with a particle size of 8μm; composite material A was 12% of the mass of iron powder;
[0104] S4. Spray the composite material B onto the surface of the ductile iron with a spraying thickness of 0.5, and perform plasma beam modification. The process is: current 30A; argon gas flow rate 5L / min; scanning speed 500mm / min, to obtain ductile iron material.
[0105] Comparative Example 3: A method for recycling scrap steel to prepare high-strength ductile iron material, comprising the following process:
[0106] Steps 1-2 are the same as in Example 1.
[0107] Step 3. Surface treatment:
[0108] Mix tungsten carbide and iron powder, ball mill, cold press, process: pressure 16MPa, duration 4h; hot press sintering, process: hot press pressure 15MPa, in argon atmosphere, at 700℃, keep warm for 160min; heat up to 1200℃, keep warm for 160min; cool to 450℃, keep warm for 100min; cool to room temperature with furnace; crush to obtain composite material with particle size of 8μm; tungsten carbide is 12% of the mass of iron powder;
[0109] S4. Spray the composite material onto the surface of the ductile iron with a spraying thickness of 0.5, and perform plasma beam modification. The process is: current 30A; argon gas flow rate 5L / min; scanning speed 500mm / min, to obtain ductile iron material.
[0110] experiment
[0111] The ductile iron materials obtained in Examples 1-3 and Comparative Examples 1-3 were taken to prepare samples, and their properties were tested and the test results were recorded:
[0112] Tensile performance test: Based on GB / T228 as the reference standard, an electronic universal tensile testing machine was used to test the tensile performance of ductile iron at a tensile speed of 4mm / min;
[0113] Impact performance test: GB / T229 is used as the reference standard, the size of the unnotched specimen is 10mm×10mm×55mm, and the impact performance of ductile iron is tested using an impact testing machine.
[0114] Microhardness test: The microhardness of ductile iron material was measured using a microhardness tester with a load of 0.2 kg and a loading time of 15 s.
[0115] Friction and wear performance test: The friction coefficient of ductile iron material was determined using a friction and wear testing machine with a load of 50N, a frequency of 2Hz, an amplitude of 5mm, a sliding speed of 20mm / s, a test time of 120min, and a total wear stroke of 144m. The friction pair was a WC grinding ball with a diameter of 8mm and a hardness of HRA94.
[0116] Table 1. Experimental data on ductile iron:
[0117]
[0118] Table 2. Experimental data on ductile iron materials:
[0119]
[0120] According to the data in the above table, we can clearly draw the following conclusions:
[0121] The ductile iron obtained in Examples 1-3 is compared with the ductile iron obtained in Comparative Example 1. The test results show that the ductile iron obtained in Examples 1-3 has higher tensile strength, yield strength, elongation, and impact work data. This fully demonstrates that the setting of the ductile iron component and the process of the present invention can improve the tensile properties and impact properties of the ductile iron.
[0122] The ductile iron materials obtained in Examples 1-3 are compared with the ductile iron materials obtained in Comparative Examples 2-3. The test results show that the ductile iron materials obtained in Examples 1-3 have higher microhardness and lower friction coefficient data. This fully demonstrates that the surface treatment process of ductile iron and the components used in the present invention can improve the surface hardness and wear resistance.
[0123] It should be noted that, in this article, relational terms such as first and second, etc. are only used to distinguish one entity or operation from another entity or operation, and do not necessarily require or imply any such actual relationship or order between these entities or operations. Moreover, the terms "include", "comprise" or any other variations thereof are intended to cover non-exclusive inclusion, so that a process method article or device including a series of elements includes not only those elements, but also other elements not explicitly listed, or also includes elements inherent to such process method article or device.
[0124] Finally, it should be noted that the above is only a preferred embodiment of the present invention and is not intended to limit the present invention. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art can still modify the technical solutions described in the aforementioned embodiments or replace some of the technical features therein by equivalents. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.
Claims
1. A method for recycling scrap steel to prepare high-strength ductile iron material, characterized in that: Including the following processes: Step 1. Smelting: Add scrap steel and carburizer into the furnace in sequence, heat and melt to 1500-1560°C until the carburizer is completely melted; add ferrosilicon and copper to form molten iron; Step 2. Spheroidizing and inoculating: add spheroidizing agent to the bottom of the spheroidizing bag, cover the spheroidizing agent with primary inoculant, pour the molten iron into the spheroidizing bag, control the temperature at 1430-1460℃, and carry out inoculation in the mold while spheroidizing; After being poured out of the furnace, a flow inoculant is added during the process to carry out flow inoculation; after cooling and forming, heat treatment is carried out to obtain ductile iron; The ductile iron is surface treated, and the specific process is as follows: S1. Mix and disperse carboxylated graphene and ammonium metatungstate solution; heat to 60-70°C, stir for 4-5h; filter and dry; Under the protection of nitrogen atmosphere, the temperature is raised to 900-950°C, and a mixed gas of hydrogen and methane is introduced at the same time, and the temperature is kept for reaction for 4-5 hours; and the mixture is cooled naturally to obtain composite material A; S2. The composite material A is mixed with boron carbide, ball-milled with ethanol, dried, and passed through a 100-mesh sieve; cold isostatic pressing and sintering are performed to obtain a composite material B; S3. The composite material B and iron powder are mixed, ball-milled, cold-pressed, hot-pressed, sintered, and crushed to obtain a composite material C; S4. Spraying the composite material C onto the surface of the ductile iron, and performing plasma beam modification to obtain a ductile iron material; The ductile iron comprises the following components: by mass percentage, C: 3.4-3.9%, Si: 2.2-3.0%, Mn: 0.3-0.6%, Cu: 0.5-0.8%, Mg: 0.03-0.06%, P: <0.10%, S: <0.03%, RE: 0.02-0.05%, N: 50-120ppm, Zr: 0.015-0.040%, and the balance is Fe; In the step 2, the spheroidizing agent is rare earth silicon iron magnesium alloy and manganese nitride, the amount of rare earth silicon iron magnesium alloy added is 1.4-2.0% of the mass of the original molten iron; the amount of manganese nitride added is 0.1-0.3% of the mass of the original molten iron; The inoculant is a zirconium-containing inoculant, and the amount added is 0.1 to 0.2% of the mass of the original molten iron.
2. The method for preparing high-strength ductile iron material by recycling scrap steel according to claim 1, characterized in that: In the mass composition of ductile iron, in terms of mass percentage, C+Si / 3=4.3~4.6%; Mn+Cu:<1.20%, Si / 2≥Mn+Cu.
3. The method for preparing high-strength ductile iron material by recycling scrap steel according to claim 1, characterized in that: In S1, the volume ratio of carboxylated graphene to ammonium metatungstate solution is 1:(5-10); the concentration of the ammonium metatungstate solution is 15-50wt%.
4. The method for preparing high-strength ductile iron material by recycling scrap steel according to claim 1, characterized in that: In S2, the mass ratio of composite material A and boron carbide is (8-10): (2.5-3.7).
5. The method for preparing high-strength ductile iron material by recycling scrap steel according to claim 1, characterized in that: In S2, the process conditions of cold isostatic pressing are: pressure 160-200 MPa, duration 180-200 s; The sintering process conditions are: vacuum, 900-950°C, heat preservation for 60-90 minutes; Under argon atmosphere, heat up to 1600-1650°C and keep warm for 60-90 min; heat up to 2150-2200°C and keep warm for 100-150 min.
6. The method for preparing high-strength ductile iron material by recycling scrap steel according to claim 1, characterized in that: In S3, the composite material B is 12-30% of the mass of the iron powder; The process conditions of cold pressing are: pressure 16-24 MPa, duration 3-4 h; The sintering process conditions are: hot pressing pressure 15-18MPa, in argon atmosphere, at 700-750°C, keep warm for 160-200min; heat up to 1200-1250°C, keep warm for 160-200min; cool down to 450-480°C, keep warm for 100-150min; cool to room temperature with the furnace.
7. The method for preparing high-strength ductile iron material by recycling scrap steel according to claim 1, characterized in that: In S4, the spraying thickness of the composite material C is 0.5 to 1.0 mm; The process conditions of plasma beam modification are: current 30-50A; argon gas flow rate 5-8L / min; scanning speed 500-800mm / min.
Citation Information
Patent Citations
Whole steel scrap QT900-5 nodular cast iron casted by smelting and casting and production process thereof
CN107974611A